1995
DOI: 10.1002/pi.1995.210360306
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric investigation of the molecular dynamics in blends: polymers with similar molecular architecture (TMPC/PC blend)

Abstract: Broad band dielectric spectroscopy was used in the investigation of the molecular dynamics and compatibility of tetramethyl polycarbonate/polycarbonate (TMPC/PC) blends. Frequency scan measurements in the range 10−2−10−5 Hz were carried out in the temperature range 50–220°C for several blends with different compositions, namely, 0, 12.5, 25, 50, 75, 87.5 and 100 wt% of TMPC. The results obtained show that these two polymers are ideally compatible over the entire composition range. The blends reveal only one co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…The miscibility should take place on a structural level bigger than the segmental level to maintain the local environment unchanged and should be small enough to give only one common T g for the miscible blend. This fact is consistent with the previous measurements for TMPC/PC 31 and TMPC/PS 42 blends.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The miscibility should take place on a structural level bigger than the segmental level to maintain the local environment unchanged and should be small enough to give only one common T g for the miscible blend. This fact is consistent with the previous measurements for TMPC/PC 31 and TMPC/PS 42 blends.…”
Section: Resultssupporting
confidence: 94%
“…The miscibility should take place on a level somewhat between the segmental and molecular level, this level must be big enough to maintain the local environment unchanged and in the same time small enough to give only one glass relaxation process for the miscible blend. This behavior is in good agreement with the previous data for TMPC/PC 31 and TMPC/PS 42 blends, where the dynamics of the β-relaxation process of TMPC was unchanged by blending.…”
Section: Molecular Dynamics Of β-Relaxation Processsupporting
confidence: 92%
See 1 more Smart Citation
“…The most important parameter determining the quality of the blends is the degree of compatibility. It is still not clear whether the components in a blend are mixed on a segmental level or on a scale somewhere between segmental and molecular [1,2]. Furthermore, different methods used in the detection of phase separation could yield different results [3,4].…”
Section: Introductionmentioning
confidence: 95%
“…It can be seen that in addition to the ThermX homopolymer possessing a greater relaxation strength than that of PC, it varies smoothly between the two homopolymers. The dielectric relaxation strength is a function of factors such as temperature, density, the number of dipoles per unit volume, and chain conformation and interaction (both intra-and intermolecular), the latter parameter being expressed in terms of g, the dipolar correlation ~oefficient.~ Katana et al3R and Mansour et al 73 found a linear change in the strength of the a relaxation of a miscible polycarbonate pair and this was ascribed to a change in the volume of cooperativity of the a relaxation as composition was altered-with a lower relaxation strength accompanying a greater cooperative motion. Naito et al39 also noted a linear variation in a miscible poly(methy1 methacrylate) (PMMA) and poly(styrene-co-acrylonitrile) (PS-co-AN) and ascribed it to the intimacy of mixing and cooperativity of motion between the component homopolymers.…”
Section: Resultsmentioning
confidence: 99%